Pinning Control for Stabilization of Boolean Networks Under Knock-Out Perturbation - Zhong, Jie; Liu, Yang; Lu, Jianquan; Gui, Weihua (IEEE transactions on automatic control, 2022)
In genetic regulatory networks, steady states represent cell types of cell death or unregulated growth, which are of significant interest in modeling networks. In this article, a pinning control intervention is studied for global stabilization of Boolean networks (BNs) under knock-out perturbation. Knock-out perturbation means that logical variables of some nodes of a BN remain 0 s. In order to reduce the impact of perturbation on stability, a pinning control approach is proposed to maintain global stabilization for the rest nodes other than those knocked out nodes, based on the network structure (the connection rule among nodes). Compared with the existing references, the proposed pinning control dramatically reduces the high computational complexity. In addition, the design of pinning controllers is based on local neighbors' information. Finally, the proposed method is well demonstrated by a mammalian cell cycle network and a network with 30 nodes.